El incumplimiento en los derechos constitucionales de los adultos mayores en el ámbito privado, afecta el derecho del sumak ka wsay. - Murillo Navarro, Gary Gustavo (2016)
The present Legal Research Project entitled "Failure to respect the constitutional rights of the elderly in the private sphere affects the law of Sumak Kawsay", carries out a study on the situation of the elderly in the effective enjoyment of their rights, Particularly in the private sphere, since the violation of his rights in practice, does not have a criminal law that punishes him. In Ecuador, this vulnerable sector of society enjoys special protection within the constitutional framework, inasmuch as it states that it will receive priority and specialized attention in the public and private spheres, especially in the field of social and economic inclusion and protection against violence. If this were to be achieved, the living conditions of the elderly would be pleasant, since they would not be discriminated against or marginalized from the enjoyment of their rights in public and private services. We know that it is the duty of the State, society and the family to give priority attention to their individual and collective needs, as is prescribed in Article 37 of the Constitution of the Republic; However, despite the fact that the full protection of their rights is legislated in many private institutions that provide public services, they are discriminated against and restricted by age or health and that they impair the exercise of their rights in conditions of equality and justice. Hence the need to carry out this legal investigation. Keywords: Elderly, Law, Fundamental Rights, Obligation.